2018
DOI: 10.1073/pnas.1801383115
|View full text |Cite
|
Sign up to set email alerts
|

Disease outbreak thresholds emerge from interactions between movement behavior, landscape structure, and epidemiology

Abstract: Disease models have provided conflicting evidence as to whether spatial heterogeneity promotes or impedes pathogen persistence. Moreover, there has been limited theoretical investigation into how animal movement behavior interacts with the spatial organization of resources (e.g., clustered, random, uniform) across a landscape to affect infectious disease dynamics. Importantly, spatial heterogeneity of resources can sometimes lead to nonlinear or counterintuitive outcomes depending on the host and pathogen syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
84
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 89 publications
(98 citation statements)
references
References 46 publications
(60 reference statements)
0
84
0
Order By: Relevance
“…Contrary, the slower and more directed spread of the disease emerging in the case of mechanistic movement decisions ensures continuous sources of both susceptible and infectious hosts (Read and Keeling , Tildesley et al ). In contrast to the homogeneous mixing assumption that all susceptible hosts have the same chance to get infected, in spatially explicit models such as ours the number of susceptible hosts in the focal and surrounding cells is of importance for transmission and persistence (Tildesley et al , White et al ). Due to the fast spread resulting from CRWs, irrespective of the underlying landscape, a considerably higher proportion of cells is simultaneously infected.…”
Section: Discussionmentioning
confidence: 99%
“…Contrary, the slower and more directed spread of the disease emerging in the case of mechanistic movement decisions ensures continuous sources of both susceptible and infectious hosts (Read and Keeling , Tildesley et al ). In contrast to the homogeneous mixing assumption that all susceptible hosts have the same chance to get infected, in spatially explicit models such as ours the number of susceptible hosts in the focal and surrounding cells is of importance for transmission and persistence (Tildesley et al , White et al ). Due to the fast spread resulting from CRWs, irrespective of the underlying landscape, a considerably higher proportion of cells is simultaneously infected.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, preserving bats' natural habitats and roosting sites (e.g. caves) is the most effective way to avoid human-bat interaction and reduces risk of exposure to pathogens (Patil et al, 2017;Plowright et al, 2011;White et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…They also concluded that overall disease prevalence typically was lower in more fragmented landscapes, in accordance with our findings for California. It should be noted that the effects of habitat fragmentation on transmission are complicated and dependent on interactions with animal movement behavior and epidemiology (White, Forester, & Craft, ).…”
Section: Discussionmentioning
confidence: 99%